Microstructure and suppressed thermal depolarisation behaviours of lead-free Na0.5Bi0.5TiO3:ZnO ferroelectric composite ceramics. (3rd April 2018) - Li, Ling; Zhu, Mankang; Wei, Qiumei; Guo, Zhihua; Zheng, Mupeng; Hou, Yudong
ABSTRACT: A 0–3 type 0.8Na0.5 Bi0.5 TiO3 (BNT):0.2ZnO lead-free ferroelectric composite ceramic structure was prepared by a solid-state oxide route. The X-ray diffraction analysis and scanning electron microscopy observation indicate that ZnO grains were scattered in the matrix consisting of BNT grains to form a (0–3) type composite structure, and a third phase Zn2 TiO4 was formed due to the reaction ability of nano-sized ZnO with NBT compositions. The temperature-dependent electrical responses show that the dielectric anomaly at around 200°C inherited from NBT itself was suppressed as ZnO is composited, and the P r of the specimen sintered at 1000°C keeps almost unchanged as the poling temperature is 175°C, while its retained piezoelectric strain d 33 value maintains 77% of the initial as exposed to 125°C annealing. These results suggest that the thermal depolarisation of BNT is suppressed due to the introduction of ZnO, even though the third phase Zn2 TiO4 exists.